2020
DOI: 10.1166/jmihi.2020.2901
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Ray Net: Automatic Diagnosis of Thoracic Diseases Using Frontal and Lateral Chest X-rays

Abstract: Computer-aided diagnosis (CAD) is an important work which can improve the working efficiency of physicians. With the availability of large-scale data sets, several methods have been proposed to classify pathology on chest X-ray images. However, most methods report performance based on a frontal chest radiograph, ignoring the effect of the lateral chest radiography on the diagnosis. This paper puts forward a kind of model, Dual-Ray Net, of a deep convolutional neural network which can deal with the front and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The approaches can be classified into two types: model-based and input-based. In model-based approaches, one idea is to design models by imitating the radiological practice [34,21,55,26] or change the model structure based on diagnostic patterns [42,20,15]. While in input-based approaches, the knowledge is treated as external inputs to calculate features [63,62,52] or to guide the final loss [12,27].…”
Section: Related Workmentioning
confidence: 99%
“…The approaches can be classified into two types: model-based and input-based. In model-based approaches, one idea is to design models by imitating the radiological practice [34,21,55,26] or change the model structure based on diagnostic patterns [42,20,15]. While in input-based approaches, the knowledge is treated as external inputs to calculate features [63,62,52] or to guide the final loss [12,27].…”
Section: Related Workmentioning
confidence: 99%
“…Depending the approaches of using medical knowledge, They can be classified into modelbased and input-based two types. In model-based types, the authors may imitate the radiological practice to design the model [20, 23, 31, 49] or change the model structure based on diagnostic patterns [11, 18, 38]. In input-based types, the knowledge is viewed as an extra input to calculate features [46, 53, 54] or to guide the final loss [9, 24].…”
Section: Related Workmentioning
confidence: 99%
“…Huang Xin and others put forward a kind of model, Dual‐Ray Net, of a deep convolutional neural network that can deal with the front and lateral chest radiography simultaneously by referring to the method of using lateral chest radiography to assist in the diagnosis used by radiologists. By comparing different feature fusion methods of addition and concatenation, they found that concatenation's fusion effect is better, with an average AUC reaching 0.778 19 . Currently, COVID‐19 is a contagious infection that has severe effects on the global economy and our daily life 20 .…”
Section: Related Workmentioning
confidence: 99%